Learning from the Best: What Can Museums in Croatia Learn from the International Museum Practice of Web 2.0 - Stublić, Helena (Array, 2011)
Since the first appearance of Web 2.0 in 1999 we have witnessed constant increase in the number of users of its services, especially the society networks and blogs. This trend has eventually encouraged the museums as well to study their possibilities and to start implementing them actively, which is borne out vividly by numerous examples from the world museums. In this paper the most representative ones will be analyzed, i.e. those which make it possible to determine the diverse purpose of using the society networks and blogs – from the promotion of the museums themselves and the cultural heritage they take care of and attracting of real visitors to communicating with virtual users as members of the community within which the museums are active. The latter usage fits into the new mission of the museums and their perception as potential promoters of social changes and active participants in various social processes. The second part of the paper will provide comparative analysis of the examples from Croatia, giving recommendations to the national museum society itself regarding the ways in which actions should be undertaken in order to make maximum use of the mentioned Web 2.0 services.